The Fabrication of Cellulose Acetate Fiber based on Empty Fruit Bunches (EFB) using Electrospinning Technique - Lalu - Suhaimi; Annisa Azzahra; Oka Pradipta Arjasa; Deni Shidqi Khaerudini (Research Center for Chemistry - LIPI, 2022)
The cellulose acetate fiber is widely applied in various fields. This study elaborates the fabrication of cellulose acetate fiber based on cellulose acetate is synthesized from cellulose contained in empty fruit bunches (EFB).